2004
DOI: 10.2174/1568026043387818
|View full text |Cite
|
Sign up to set email alerts
|

The Central Role of Angiotensin I-Converting Enzyme in Vertebrate Pathophysiology

Abstract: Genomic epidemiologic data, increasingly supported by clinical outcomes results, strongly suggest that overactivity of angiotensin I-converting enzyme (ACE) may underlie most age-related diseases. Angiotensin II, the main product of ACE, is a pleiotropic hormone, capable of serving as a neurotransmitter, growth factor, angiogenesis factor, vasoconstrictor, pro-thrombotic agent, and cytokine. So it is perhaps not surprising that the ACE D/D genotype is associated with several major psychiatric diseases, most ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 226 publications
(262 reference statements)
1
17
0
Order By: Relevance
“…Although the survival of patients with chemotherapyresistant pancreatic cancer is less than four months and cachexia is common, once she began taking quinapril, her appetite improved dramatically, and her condition remained excellent for 12 months. Furthermore, her CA-19 level dropped steadily to a nadir of 394 U/ml, seven months after starting quinapril [104]. This phenomenon is similar to our experience with ARB treatment for HRPC patients, and ACE inhibitors and ARBs appear to exert their anticancer effects on cancer cells by similar mechanisms.…”
Section: Pancreatic Cancersupporting
confidence: 82%
See 1 more Smart Citation
“…Although the survival of patients with chemotherapyresistant pancreatic cancer is less than four months and cachexia is common, once she began taking quinapril, her appetite improved dramatically, and her condition remained excellent for 12 months. Furthermore, her CA-19 level dropped steadily to a nadir of 394 U/ml, seven months after starting quinapril [104]. This phenomenon is similar to our experience with ARB treatment for HRPC patients, and ACE inhibitors and ARBs appear to exert their anticancer effects on cancer cells by similar mechanisms.…”
Section: Pancreatic Cancersupporting
confidence: 82%
“…Ang-II is a potent cytokine, which can induce the synthesis of inflammation-related cytokines, macrophage migration inhibition factor (MIF), TNFα, monocyte chemoattractant protein-1 (MCP-1) and TGFβ etc. [104]. The AT1 receptor, a component of RAS, is expressed ubiquitously in the human body, and specifically is abundant in several cancer tissues as mentioned above.…”
Section: Role Of Ang-ii In Inflammationmentioning
confidence: 99%
“…ACE plays a vital role in the metabolism of biologically active peptides and is a pleiotropic hormone, capable of serving as a neurotransmitter, growth factor, angiogenesis factor, vasoconstrictor, prothrombotic agent and cytokine. 49 ACE activity was increased in rat lungs following wholebody irradiation. 50 Expression of dopamine receptor D 3 has been reported in peripheral mononuclear cells after radiation exposure, and it has been suggested that the expression of neurotransmitter receptor is an indicator of neuronal damage after exposure to radiation.…”
Section: Discussionmentioning
confidence: 91%
“…Surprisingly, it has been reported that quinapril, an angiotensinconverting enzyme inhibitor (ACEI), was useful in a patient with advanced-stage pancreatic cancer. 17 After the patient started quinapril, although her carbohydrate antigen (CA)19 level rose and later dropped, her condition improved dramatically and remained excellent for an additional 12 months. This clinical course is similar to those of our patients with advanced HRPC treated with an ARB.…”
Section: Discussionmentioning
confidence: 99%